2020
DOI: 10.15632/jtam-pl/127391
|View full text |Cite
|
Sign up to set email alerts
|

Stability of transverse vibration of drillstring conveying drilling fluid

Abstract: In this paper, an analytical model is proposed to predict lateral vibration of a drillstring in a vertical well. The effect of parameters, such as stiffness of spring, average weight on bit (WOB), amplitude of fluctuating WOB and so on, on the dynamic stability of the drillstring is discussed. It is found that the interaction between the drillstring and drilling mud has a great influence on drillstring buckling and dynamics. For constant drilling pressure, the mud flow rate stabilizes the drillstring under cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…After the reservoir shale imbibes the fluid, the mechanical characteristics change of hydration is obvious, and microscopically, it promotes the generation, propagation, and connection of secondary microcracks. In terms of macroscopic mechanical properties, the strength of shale decreases, and the Young's modulus reduces [11] (Figure 4).…”
Section: Reservoir Shale Characteristics Marine Shale In Southmentioning
confidence: 99%
See 1 more Smart Citation
“…After the reservoir shale imbibes the fluid, the mechanical characteristics change of hydration is obvious, and microscopically, it promotes the generation, propagation, and connection of secondary microcracks. In terms of macroscopic mechanical properties, the strength of shale decreases, and the Young's modulus reduces [11] (Figure 4).…”
Section: Reservoir Shale Characteristics Marine Shale In Southmentioning
confidence: 99%
“…In situ stress coordinate transformation equation: Figure 4: Changes in elastic modulus before and after soaked in water [11]. 4 Geofluids…”
Section: Coordinate Transformation Of In Situ Stressmentioning
confidence: 99%
“…The performance of the developed models was verified through comparisons with field test results of stick-slip vibration. Taking into account the fluid power of drilling mud, Tang et al [9] established the control equation of drill string vibration by using the micro element method, and studied the dynamic stability of the drill string system. It was found that the flow rate of drilling fluid would affect the stiffness and damping of the drill string system at the same time.…”
Section: Introductionmentioning
confidence: 99%